The Development of the European Union State Aid Rules in the Energy Sector - Giannini, Eugenia; Makri, Evi (Technical Annals, 2023)
The present paper presents the developments on the framework that governs the investments on the energy sector, focusing on competition law and the support to renewable energy sources through state aid. The researchers examine the developments of the state aid cases that have been under assessment by the European Commission over the course of the years and particularly, those regarding investments on renewable energy sources (RES) after the announcement of the European Green Deal, in late 2019. In addition to the above, the decisions of the European Commission and its tendency to not raising any severe objections, in general, against such cases of support schemes provided as state aid, are reviewed in parallel to the energy policy of the European Union, as it has been recently shaped in order to promote the increase of the use of RES in the EU Member States. Besides, the increased penetration of RES for the European Union, bares multiple benefits since, apart from playing a key role in the Union’s policy to tackle climate change and its severe consequences, it also contributes in the extended efforts of the EU Member States to minimize their dependence on energy products highly imported from Russia, such as natural gas, in the shadow of the recent war in Ukraine. Under that prism, the present paper provides a coherent and consistent examination of the ways in which state aid can be accepted by the European Commission, within the broader framework of the Competition protection in the EU, as well as the ways in which it can be even considered not to cause any severe distort of competition. The above are mainly concluded in case in which the support provided through such schemes tends to promote the development of activities that serve - on a high degree - the common interest, both on the national and the European level. Thus, the development of renewable energy technologies in the European energy sector and their enhancement towards greening the Union’s energy mix while turning it into a more resilient and independent one, can be considered as such a type of activities, as it will be further analyzed in this paper.